Analyzing the diffusion of innovation in health communication: a content analysis of the healthy family talk show - Aditia, Rafinita; Shah, Prisha; Fadhilah, Madu Sarah (Jurnal Cakrawala Promkes, 2025)
This study examines the role of innovation diffusion in health communication through social media platforms and radio broadcasts by the Ministry of Health of the Republic of Indonesia, focusing on the Healthy Family Talkshow program. The research uses Rogers’ Diffusion of Innovation theory to assess how health information is disseminated and adopted across different audience segments. The program, broadcast on Instagram (@kemenkes_ri) and the Ministry of Health's radio network, aims to provide credible, relevant, and easily understood health information. A content analysis of 35 Instagram posts and radio broadcasts from October to November 2024 was conducted to evaluate the effectiveness of communication and its impact on audience perceptions and behaviors. The findings indicate that the program successfully addressed key health topics, such as disease prevention, vaccination, and healthy lifestyles, reaching a broad audience. The dual-platform approach offered flexibility, allowing individuals to choose their preferred communication channel, which led to high engagement through views, comments, and shares. However, the study also identified challenges, including technological barriers, limited internet access in rural areas, which affected participation, and demographic disparities in adoption rates. Younger, more educated audiences adopted the information more quickly, while older individuals required additional support to implement health recommendations. Despite these challenges, the findings demonstrate the potential of integrating social media and radio to enhance health communication. This research underscores the importance of addressing technological and demographic gaps to improve the effectiveness of health information dissemination. The study provides valuable insights for developing inclusive health communication strategies to increase public health awareness and drive behavioral change.